Gender Role Reversal, Female Solidarity, and Fallen Women in Oscar Wilde's Plays - Milosavljević, Marija (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Wilde’s plays The Importance of Being Earnest, A Woman of No Importance, Lady Windermere’s Fan and Salomé all feature female characters and themes relevant to the domains of research of feminist literary theory, including relationships between men and women, marriage, the complexity of female characters, their treatment in literature, gender roles and how they are portrayed. This paper explores the themes of role reversal, female solidarity and fallen women with the aim of showing that Wilde’s works were progressive for their time in terms of pointing out problematic societal expectations and norms.In The Importance of Being Earnest, Wilde satirized the gender roles of the Victorian society and how men had power over women and their choices, while in the plays A Woman of No Importance, Lady Windermere’s Fan and Salomé, the main characters are fallen women, a stereotype the Victorian society invented to mark women they considered impure. A Woman of No Importance and Lady Windermere’s Fan are plays about the struggles of fallen women who made mistakes in the past and formed important friendships with other female characters, while the tragedy Salomé tells the tale of a woman who falls and dies as a consequence of her fall. Additionally, the paper will examine closely related themes, such as motherhood, sexuality, and negative gender stereotypes related to the one of the fallen women.
Keywords: Wilde; feminism; female characters; gender roles; sexuality